Pengaruh Kepemimpinan Visioner Kepala Sekolah dan Iklim Sekolah Terhadap Kinerja Guru SMP Swasta di Sumatera Utara - Ellyana Ellyana (Dhammavicaya : Jurnal Pengkajian Dhamma, 2025)
This study investigates the impact of visionary leadership (X1) and school climate (X2) on teacher performance (Y) in private junior high schools (SMP) in North Sumatra. The study is motivated by the varying levels of teacher performance in private schools within the region, which are believed to be influenced by the principal's leadership approach and the prevailing school climate. Recognizing the crucial role of teacher performance in student-centered education, this research provides a comprehensive analysis of the factors affecting it. A quantitative research approach employing a survey method was adopted. Data were gathered through questionnaires completed by 145 permanent foundation teachers in North Sumatra. Multiple linear regression analysis was applied to assess the influence of the two independent variables on teacher performance. The findings revealed a strong correlation between visionary leadership and teacher performance, with a Pearson correlation coefficient of 0.645. Similarly, school climate demonstrated a strong association with teacher performance, reflected in a correlation value of 0.727. Moreover, visionary leadership was found to have a positive and significant impact on teacher performance, with a regression coefficient of 0.286 and a t-value of 4.941, exceeding the t-table value of 1.656. Likewise, school climate significantly contributed to teacher performance, with a regression coefficient of 0.467 and a t-value of 8.036 > t-table 1.656. Collectively, both variables explained variations in teacher performance, as indicated by an F-test significance of 0.000 < 0.05 and an F-value of 105.699 > F-table 3.06. These findings highlight the essential role of visionary leadership and a positive school climate in enhancing teacher performance in private schools in North Sumatra.